Aging Negatively Impacts DNA Repair and Bivalent Formation in the C. elegans Germ Line - Raices, Marilina; Bowman, Richard; Smolikove, Sarit; Yanowitz, Judith L. (Frontiers in Cell and Developmental Biology, 2021)
Defects in crossover (CO) formation during meiosis are a leading cause of birth defects, embryonic lethality, and infertility. In a wide range of species, maternal aging increases aneuploidy and decreases oocyte quality. In C. elegans which produce oocytes throughout the first half of adulthood, aging both decreases oocytes quality and increases meiotic errors. Mutations in genes encoding double-strand break (DSB)-associated proteins get more severe with maternal age suggesting that early meiosis reflects a particularly sensitive node during reproductive aging in the worm. We observed that aging has a direct effect on the integrity of C. elegans meiotic CO formation, as observed by an increase of univalent chromosomes and fusions at diakinesis, with a considerable increase starting at 4 days. We also characterize the possible causes for the age-related changes in CO formation by analyzing both steady-state levels and kinetics of the ssDNA binding proteins RPA-1 and RAD-51. Profound reductions in both RPA-1 and RAD-51 foci numbers suggests that both DSB formation and early meiotic repair are compromised in aging worms. Using microirradiation and -irradiation to induce exogenous damage, we show specifically that recruitment of these homologous recombination proteins is altered. Repair defects can be seen in two-and-one-half day-old adults making the loss of germline repair capacity among the earliest aging phenotypes in the worm.